26.5k views
5 votes
Which shows the correct way to divide 2x^3 + 6x^2 – 2x – 5 by x + 3 using synthetic division?

User TechTurtle
by
5.4k points

2 Answers

1 vote
Simplifying
x4 + -2x3 + 6x2 + -2x = 5

Reorder the terms:
-2x + 6x2 + -2x3 + x4 = 5

Solving
-2x + 6x2 + -2x3 + x4 = 5

Solving for variable 'x'.

Reorder the terms:
-5 + -2x + 6x2 + -2x3 + x4 = 5 + -5

Combine like terms:
5 + -5 = 0 -5 + -2x + 6x2 + -2x3 + x4 = 0

The solution to this equation could not be determined
User Mohit Bhansali
by
5.8k points
3 votes

2x^3 + 6x^2 -2x - 5
by x+3 , negative -3

-3
|2 |6 |-2 |-5|
|2 |0 |-2 |1 |

2x^2+0x-2+(r1)=2x^2-2+(1)/(x+3)


(2x^3 + 6x^2 -2x - 5)/(x+3)=2x^2-2+(1)/(x+3)
User Arovit
by
5.6k points